Approximate, analytical determination of steady state temperature distribution in thermally orthotropic rods. - Laura, P. A. A.; Gutiérrez, G. H.; Sánchez Sarmiento, G. (Aplied science publishers, 1979)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina